2016
DOI: 10.1101/gr.195800.115
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem genetic screening for the identification, verification, and reporting of genetic variants contributing to the sudden death of the young

Abstract: Each year in the United States, thousands of cases of sudden and unexpected deaths of infants, children, and young adults are assigned an undetermined cause of death after postmortem investigation and autopsy. Heritable genetic variants have been suggested as the cause of up to a third of sudden death (SD) cases. Elucidation of the genetic variants involved in SD cases is important to not only help establish cause and manner of death of these individuals, but to also aid in determining whether familial genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
3
19
0
1
Order By: Relevance
“…From a cohort of 10 infants with SIDS, we identified 2 cases with heterozygous SCN1A variants. The variants we report, similar to those we have cited, are predicted to be pathogenic using in silico assessments. These predictions are further strengthened by association with previously reported cases with epilepsy, location of the variants in critical, disease‐associated domains of the protein, and functional evidence that the variants present in both cases exhibit partial loss of function.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…From a cohort of 10 infants with SIDS, we identified 2 cases with heterozygous SCN1A variants. The variants we report, similar to those we have cited, are predicted to be pathogenic using in silico assessments. These predictions are further strengthened by association with previously reported cases with epilepsy, location of the variants in critical, disease‐associated domains of the protein, and functional evidence that the variants present in both cases exhibit partial loss of function.…”
Section: Discussionsupporting
confidence: 83%
“…SCN1A ‐related mechanisms have been postulated to underlie a risk of SUDEP in patients with Dravet syndrome, with evidence from rodent models providing supporting evidence . In recent reports, SCN1A was not included in the panel of genes interrogated . A report of SCN1A Leu61Pro in association with SUDC underscores the potential for SIDS and SUDC to share SCN1A‐related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While reports have estimated that up to 15% of SIDS were related to specific genetic variants [e.g., Ref. (154)], a recent study that sequenced the full exons of 64 genes associated with sudden death in the largest known cohort (351) of infant and young sudden death decedents reported that less than 4% of unexpected deaths were associated with a pathogenic genetic variant (155). These results suggest that many pathogenic variants involved in SIDS are unknown or, most likely, that pathogenic variants play a minute role is SIDS.…”
Section: Introductionmentioning
confidence: 99%
“…We have published a more detailed analysis of state laws and the implications of differences elsewhere (Moore et al 2016). In this paper, we describe the experiences and reflections of the Molecular Autopsy Consortium of Houston (MATCH), a collaboration between the Harris County Institute of Forensic Sciences (an integrated operation including Medical Examiner services and Crime Laboratory services) and Baylor College of Medicine, which conducted genetic analysis on a large cohort of 351 deceased infants, children, and young adults (age range 0-37) in an effort to determine the cause and manner of death (Methner et al 2016).…”
mentioning
confidence: 99%